Perspektif Dramaturgi Pada Komunikasi Antar Budaya Indonesia-Australia - Moch. Armien Syifaa Sutarjo; Anisa Diniati; Sri Dewi Setiawati (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Individuals meet and communicate with other individuals in various social contexts every day. They interact and communicate by bringing with them the patterns of thinking, feeling and behavior they have learned during their lives. All forms of communication must have a cultural background, and the differences that exist in the communication process become a major obstacle. This study aims to discover how communication exists amid cultural differences between Indonesia and Australia so that the communication process continues to run well, using Erving Goffman's Dramaturgy theory approach, with the concept of backstage and frontstage. This research is qualitative research using a phenomenological approach. Data was collected through in-depth interviews, observation and documentation studies. The results of this study indicate that in the preparation stage (backstage), before directly meeting and communicating with Australian families, they used two kinds of information sources: Internet References and Human References. In their daily interactions, in presenting the frontstage, there were two kinds of characters shown by the speakers, namely Westernized Indonesian and Indonesianized-Indonesian.